Analysis of Factors Affecting the Increase in Income of Micro, Small and Medium Enterprises (MSME) in Padangsidimpuan City with Entrepreneurship as an Intervening Variable - Darwis Harahap; Ikhwan Maksum; Rukiah Rukiah (Universitas Muhammadiyah Surabaya, 2023)
This research is motivated by the findings of researchers regarding the phenomenon where MSME actors in the city of Padangsidimpuan in general have not maximized access to financial inclusion, low self-efficacy, low motivation and do not yet have an entrepreneurial spirit and character. This research uses quantitative research methods. The research sample was 177 MSME actors in Padangsidimpuan City. The data collection instrument was carried out by distributing questionnaires to respondents. Then data analysis uses the outer model test, inner model and hypothesis testing. The results of the study show (a) there is a significant effect of financial inclusion on entrepreneurship b) there is no effect of efficacy on entrepreneurship (c) there is a motivational effect on entrepreneurship (d) there is no effect of religiosity on entrepreneurship (e) there is no effect of entrepreneurship on MSME income in the city of Padangsidimpuan (f) there is a significant effect of financial inclusion on MSME income in the city of Padangsidimpuan (g) there is no efficacy effect on MSE income in the city of Padangsidimpuan (h) there is no motivational effect on MSME income in the city of Padangsidimpuan (i) there is no effect of religiosity on MSME income in the city of Padangsidimpuan (j) there is no effect of financial inclusion on the income of MSMEs in the city of Padang Sidimpuan through entrepreneurship (k) there is no efficacy effect on MSME income in the city of Padangsidimpuan through entrepreneurship (l) there is no motivational effect on MSME income in the city of Padangsidimpuan through entrepreneurship (m) there is no effect of religiosity on MSME income in Padangsidimpuan City through entrepreneurship.